Design, synthesis and catalytic performance of vanadium-incorporated mesoporous silica KIT-6 catalysts for the oxidative dehydrogenation of propane to propylene. Issue 15 (29th April 2016) - Liu, Qinglong; Li, Jianmei; Zhao, Zhen; Gao, Manglai; Kong, Lian; Liu, Jian; Wei, Yuechang
Abstract : The vanadium-incorporated KIT-6 catalysts synthesized by combining a direct hydrothermal method with a pH adjusting method show superior catalytic performance in the oxidative dehydrogenation of propane to propylene. Abstract : A series of vanadium-incorporated mesoporous materials V-KIT-6 with different vanadium contents were synthesized by combining a direct hydrothermal method with a pH adjusting method and applied as catalysts for the oxidative dehydrogenation of propane. The structures of the catalysts were characterized by various techniques including N2 adsorption–desorption, XRD, TEM, SEM, UV-vis DRS, H2 -TPR and Raman spectroscopy. The results reveal that the pH value plays a key role in the structure of the catalysts and the incorporated content of vanadium in the synthesis process of V-KIT-6 materials. The framework-incorporation of various contents of vanadium under mild acidic conditions (pH = 5) preserves the well-defined 3D interconnected mesoporous features of KIT-6 and promotes the dispersion of vanadium oxide species. The V-KIT-6 catalysts show much higher catalytic selectivity and productivity to propylene in the oxidative dehydrogenation of propane than the corresponding supported vanadium catalyst. The highest selectivity sum of C2 H4 + C3 H6 (70.2%) is obtained over the 5V-KIT-6 catalyst; meanwhile, a high space-time yield (STYC3 H6 ) of 3.91 kgpropylene kgcat −1 h −1 is obtained. The superior catalytic performance of the V-KIT-6 catalysts in the oxidative dehydrogenation of propane can be ascribed to the high concentration of highly dispersed active sites as well as the favorable property of mass transfer and accessibility of the active sites to the reactant molecules in the 3D interconnected mesopores.